THREATS TO FINANCIAL SAFETY OF THE MARKET OF INSURANCE SERVICES AND METHODS OF ITS PROVIDING - S. Lobanov (Вестник университета)
Threats to financial safety of the market of insurance services and methods of it's providing are considered. The article gives a definition of a concept of a threat to financial safety of the market of insurance services as real or potential possibility of manifestation of the destructive impact of various factors on a financial state and development of objects of financial safety giving this object to certain economic, financial and social psychologically damage. The description of standard and legal, financial and economic, production and technological, infrastructure and social and psychological methods of ensuring financial safety in relation to the corporate market of insurance services in Russia and abroad is provided.